PENGARUH MODEL DISCOVERY LEARNING BERBANTU KARTU MASALAH PADA MATERI GERAK LURUS TERHADAP HASIL BELAJAR SISWA KELAS X IPA SMA N 1 MRANGGEN TAHUN PELAJARAN 2014/2015 - Wisnu Kemuning; Nur Khoiri; Sigit Ristanto (Jurnal Penelitian Pembelajaran Fisika, 2015)
This study aims "To determine whether there is influence of discovery learning model assisted problem card in a straight motion on the results of study X science class SMA Negeri 1 Mranggen academic year 2014/2015". The population in this study were all class X  SMAN 1 Mranggen Academic Year 2014/2015. Sampling using cluster random sampling technique with the normal condition of all classes and homogeneous. Sampling results obtained by X-class science experiment 1 as a class were treated when learning takes place using discovery learning model and problem cards for class X IPA 2 as the control class is given learning using discuss learning group. Based on the final analysis of the t-test showed that t = 4.6738 while the table = 1.671 with a significance level of 5%. Because thitung > ttable is 4.6738> 1.671 it can be interpreted that the average student learning outcomes experimental class better than the class control. The average value of the experimental class is 77.6316 and 70.6579 as control class. Pursuant to the results of this study concluded that there are significant of discovery learning model assisted problem card in a straight motion on the results of study X science class SMA Negeri 1 Mranggen academic year 2014/2015.